Morphofunctional Characteristics of Pelvic and Thigh Muscles of Bornean Orangutan (Pongo pygmaeus) - Yasmin Nadhiva Narindria; Supratikno; Savitri Novelina; Danang D. Cahyadi; Chairun Nisa'; Srihadi Agungpriyono; Nurhidayat - Nurhidayat (Jurnal Biologi Papua, 2025)
Primates have various type of locomotion according to adaptation to their habitat. Orangutans, gorillas, and chimpanzees are primates belong to the same family, Hominidae. Despite their anatomical and physiological similarities, there are differences in adaptation and life behavior that cause differences in the distinctive anatomical structures of all three hominids. This research aims to study the anatomical characteristics of Bornean orangutans’ pelvic and thigh muscles associated with the function and daily behavior. This research was conducted by observing the morphology of the orangutan’s pelvic and thigh muscles, also observing the orangutans’ arboreal and terrestrial behavior through video observations. The results showed that the pelvic muscles and extensor muscles of the hind limb of the orangutans were less developed than in gorillas and chimpanzees. Orangutans have well-developed m. scansorius to compensate the absence of m. tensor fasciae latae. Musculus ischiofemoralis in orangutans has a unique structure because it is separated into a distinctive muscle. The absence of m. adductor minimus is associated with the orangutans’ standing posture that more open than in gorillas. The differences in the development of these muscles are due to the adaptation of the orangutans’ arboreal behavior to its habitat.